A calorimetric technique of measuring low heat of solution - Crouse, Karen Anne (1983)
A simple calorimeter has been assembled specially for the measurement of low heats of solution. Decanoic acid was used as a thermostatic material. A change in temperature induces an emf in a copper constantan thermocouple. This small voltage is measured with a microvoltmeter, amplified and recorded